2010
DOI: 10.1310/hct1104-220
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Nandrolone and Testosterone in Adult Male HIV Patients With AIDS Wasting Syndrome (AWS): A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Our trial demonstrates the superior therapeutic effects of nandrolone in male AWS patients, including the androgen deficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Information on the diaphragm in rodent models of ALS is limited and has mainly been obtained in the transgenic rat model (Holzbaur et al, 2006;Lladó et al, 2006;Lepore et al, 2010), and the NMJ fine structure has not been analyzed in these studies. Moreover, we investigated the effects of treatment with nandrolone on NMJs of mSOD1 diaphragm; this anabolic steroid is widely employed in the treatment of muscle wasting associated with several pathological conditions in humans (Adachi and Takayanagi, 2008;Macdonald et al, 2007;Sardar et al, 2010). Nandrolone is also still one of the anabolic steroids most frequently used as performance-enhancing drug by athletes, as well as by adolescent non-athletes, though prohibited by doping control regulations (Maravelias et al, 2005;Hemmersbach and Grosse, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the diaphragm in rodent models of ALS is limited and has mainly been obtained in the transgenic rat model (Holzbaur et al, 2006;Lladó et al, 2006;Lepore et al, 2010), and the NMJ fine structure has not been analyzed in these studies. Moreover, we investigated the effects of treatment with nandrolone on NMJs of mSOD1 diaphragm; this anabolic steroid is widely employed in the treatment of muscle wasting associated with several pathological conditions in humans (Adachi and Takayanagi, 2008;Macdonald et al, 2007;Sardar et al, 2010). Nandrolone is also still one of the anabolic steroids most frequently used as performance-enhancing drug by athletes, as well as by adolescent non-athletes, though prohibited by doping control regulations (Maravelias et al, 2005;Hemmersbach and Grosse, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] One study, with a Jadad score of 3, showed no change in weight or estimates of body fat (triceps and scapula skinfold thickness). [ 105 ] In studies of HIV-positive men with weight loss, 3 of 6 studies (all of which had Jadad scores of 4 or 5) showed an increase in weight with testosterone treatment,[ 99 , 101 , 106 ] and all 4 studies that measured muscle mass showed an increase. [ 41 , 99 101 ]…”
Section: Resultsmentioning
confidence: 99%
“…In both studies the intervention was associated with weight gain [ 18 , 19 ]. A randomised comparison of nandrolone, testosterone, or placebo for adult HIV patients with HIV wasting syndrome showed superior weight gain and improvement in BMI and quality of life from nandrolone [ 20 ]. Patients with COPD were given 50 mg fortnightly for 4 doses with improvement of muscle function and exercise capacity.…”
Section: Discussionmentioning
confidence: 99%